Behavior of steel members subject to combined bending and torsion - Venkateswaran Balakrishnan (2009)
Steel members subjected to combined bending and torsion usually results in many complications which are difficult to design for. Thus, there is little or no guidance on steel members subjected to this combined loading in BS5950 design code as the code explicitly provides for very few cases of combined loading such as combined bending and axial force, and biaxial moments. Moreover, the eccentric loading experiment brings about concerns such as the beam ‘flying off’ and the loading equipment dropping during the experiment. The aim of this project is to observe the behavior of two back to back lipped channels under combined bending and torsion, and to critically analyse the combined effects through performing two laboratory experiments in torsion fixed, warping fixed support situations. An eccentric load is applied off-center of the beam and the loading is increased until the entire member fails completely in combined bending and torsion. This project additionally aims to evaluate both back to back and lip to lip connected channels and provide a feasible alternative for the connected beams to be used as floor beams as part of a rapid deployable structure to be used in Sichuan and possibly other disaster prone areas. The project is broken down into four major phases. The first phase involves conducting extensive literature review on the subject matter and performing theoretical calculations on two back to back lipped, C20019 (203x76) beams. The BS5950 calculations are performed and the connection detail has been designed according to Part V. The second phase involves brainstorming, choosing and drawing up the most feasible, inexpensive and simple connection detail for the back to back design. Eventually, a combination of tek screws, fasteners and welding of fabricated metal plates at critical spots was chosen for the connection detail. The next phase is to analyze and finalize the detailed experimental procedures and set-up which address the problems and safety concerns that arises out of an eccentric load. The final phase involves the theoretical and the experimental results being analyzed and correlated and a suitable design to be chosen and recommended for the floor beams as part of a rapid deployable shelter. The back to back design of the beam was thus, found to be the most suitable alternative due to the relatively easier connection detail and higher failure load compared to that of the lip to lip section design.